Technological aspects of finishing 3D-shaped wooden products by UV-cured compositions - Yarish , Oksana (Forestry, Forest, Paper and Woodworking Industry, 2024)
Due to its high performance, low environment pollution and energy saving technology UV curing of the coating jumps to the word of 3D shaped wooden articles. The main difference of curing 2D and 3D articles are different distance between cured surface and UV source. Angles of irradiation failing on the surface are also different. There are few approaches to resolve this issue. First one is LaroluxTM UV curing of coatings in carbon dioxide. This method eliminates influence of oxygen inhibition of free radicals UV curing mechanism and thus distance between lamp and substrate is of minor importance. UV lamps could also be replaced by ones with lower energy consumption. Simple reflectors are also used to illuminate areas hidden from direct rays. Another approach is replacing of traditional mercury arc UV lamps and reflectors by set ups with multiple light sources. New revolutionary tendency is appearing on the market UV Light Emitting Diodes (UV LED). These devices joined in Semiconductor Light Matrix (SLM), have a lot advantages compare to arc lamps. Most of them are very long lifetime, very low energy consumption (5–6kW/light source), instant on/off, no IR radiation, no ozone formation during UV curing. These UV light sources are applicable for curing pigmented products made from wood materials and heat-sensitive plastic materials. Phosen Inc use state of the art MOEMS (microoptoelectro-mechanical system) technology in design of their LED SLM. Tikkurila Coatings probed UV LED SLM in their UVITEC® 2D Curing System for Wood and PVC UV Curable Coatings. Multi lamp set ups requires more precision adjustment of lamps position regarding curing surface. Computer simulations help to do this. Program VirtualPaintShop developed by CADFEM GmbH include module VPS/UV. This module calculates irradiation dose on different areas of the cured object in dependence of the Lamp type, UV absorption eflection of the coating, object and light source relative moving. Lighting conditions and therefore quality of the coating can also be estimated on the real set up without coating application. For this multiple UV radiometers could be attached to the different points on the surface of complex 3d shape. Information collected from these radiometers together with computer simulation gives possibility precisely adjust position of fixed lamps or optimize moving of mobile ones. As many trials as needed could be run without wasting of articles and coating materials. 3DCURE® sensors manufactured by EIT (Sterling, Virginia, USA) are suitable for such kind of adjustments. As robotic systems are become chipper and more powerful they also could be considered as replacement for multi lamp systems. The amount of investments and savings depends of the number of UV laps replaced by robot manipulated by single lamp. In general case technology line with 6 UV lamps is replaceable by robotic system from the point of costs saving.